Peranan Industri Pembongkaran Kapal Ship Scrapping dalam Ekonomi Sirkular Maritim - Windya Sara Yulius; Eliyanti Agus Mokodompit (Yayasan Cendekia Gagayunan Indonesia, 2026)
This study aims to analyze the strategic role of the ship scrapping industry in supporting a sustainable maritime circular economy ecosystem. The research employs a qualitative method with a literature review approach, utilizing content analysis of academic journals, industry reports, and international regulations. Data were gathered from various authoritative sources to identify best practices and global standards in ship lifecycle management. The results indicate that the ship scrapping industry serves as a vital hub for secondary material recovery, reducing reliance on virgin raw materials and facilitating global fleet renewal. However, the study finds a significant disparity in the implementation of safety and environmental standards as mandated by the Hong Kong Convention; countries such as Turkey and China lead in compliance, while major recycling hubs in South Asia remain in a transitional phase. As a prominent maritime nation, Indonesia possesses significant potential to integrate this industry into its national circular economy agenda through the development of eco-friendly shipyard infrastructure. This study recommends the synchronization of national regulations with international standards to optimize the potential of the maritime circular economy while mitigating environmental risks associated with ship recycling activities in Indonesia.